Kontribusi lembaga sertifikasi nazhir terhadap optimalisasi pengelolaan wakaf - Faujiah, Ani (Alkasb: Journal of Islamic Economics, 2024)
This research aims to analyze the contribution of Nazhir certification institutions to the optimization of wakaf management. The study adopts a qualitative research method with a descriptive approach. Informants include certified Nazhir and wakaf institutions from specific regions. The sampling was purposive, focusing on Nazhir with experience in wakaf management and certification bodies actively involved in the process. Data collection methods encompass in-depth interviews, observation, and documentation, with semi-structured interview guides serving as research instruments. Triangulation of sources and methods was used to ensure data validity, and the analysis proceeded through data reduction, presentation, and conclusion verification. The findings reveal that Nazhir certification institutions play a significant role in enhancing Nazhir’s competence and accountability in managing wakaf. Certification boosts public and donor trust, while also improving transparency and professionalism in the management of wakaf assets. The study underscores the need for a stronger certification system for Nazhir to optimize wakaf management. Researchers recommend expanding the scope of certification institutions and increasing access for Nazhir in various regions. Strengthening regulations that support Nazhir certification is also vital to ensure the sustainability of a professional and accountable wakaf management system.